A fuzzy multi criteria risk assessment based on decision matrix technique: A case study for aluminum industry. (March 2016) - Gul, Muhammet; Guneri, Ali Fuat
Abstract: Decision matrix risk-assessment (DMRA) technique is a systematic approach widely used in the Occupational Health and Safety (OHS) risk assessment. In a typical matrix method approach, a measure of risk value is obtained by evaluating two risk factors as the likelihood of a hazard and the severity of the hazard when it arises. In this paper, a fuzzy approach enabling experts to use linguistic variables for evaluating two factors which are the parameters of matrix method is proposed to deal with shortcomings of a crisp risk score calculation and to decrease the inconsistency in decision making. The parameters likelihood and severity related to the hazards in an aluminum plate manufacturing plant are weighted by using Fuzzy Analytic Hierarchy Process (FAHP), then the orders of priority of 23 various hazard groups are determined by using Fuzzy TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method. As a follow-up study of the case application, the proposed risk assessment methodology is applied for hazard types in each department of the plant. Depending on the hazard control hierarchy, control measures are overtaken for the hazards that are placed at first of intra-department rankings. Highlights: A fuzzy multi criteria risk assessment methodology enabling OS experts to use linguistic variables is proposed. A case study in an aluminum plate manufacturing plant in Turkey is carried out. The likelihood and severity which are the parameters of DMRA technique are weighted by using fuzzy AHP. The orders of priority of 23 various hazard groups are determined by using fuzzy TOPSIS method. A follow-up study of the case application for hazard types of each department in the plant is performed.